NUTRIÇÃO E RENDIMENTO DO MILHO PARA SILAGEM EM SISTEMAS DE MANEJO E USO DO SOLO APÓS CALAGEM - Duda, Luana (2014)
Researches has been carried out focusing to improve nutrients use efficiency, avoid degradation of environmental resources, increase crop yields and maximize profitability of the agricultural production system. In this sense, integrated crop-livestock systems have been characterized by different dynamics compared to conventional crops systems, mainly because of the more efficient use of inputs due to high nutrient stored in the soil. The no-tillage (NT) associated with integrated crop-livestock (ICL) has been an alternative for intensification of soil use in Southern Brazil. In this issue, there are a lot of farmers have been cropped maize for silage production in the summer and annual ryegrass for various purposes (cover crop and animal feed). The maize due its yield potential, chemical composition and nutritional value, among other factors, constitutes one of the most important cropped and consumed cereal in the world and, moreover, this crop can be used for market manufacturing animal feed and human food. In this work were (i) evaluate the effects of liming on soil management systems (conventional tillage – CT, minimum tillage – MT, no-tillage – NT, and chiseled no-tillage – CNT) about the accumulated nutrients in maize aerial part; (ii) evaluated the dry matter (DM) and silage yields taking into consideration the previous crop annual ryegrass for different uses (cover crop – C, grazing – G, and silage – S) during the winter. The experiment was carried out Field Demonstration and Experimental (CDE) of the ABC Foundation, in the municipality of Castro-PR, in a clayey Haplohumox. The experimental design was a randomized complete block with split plots and four replications. In main plots (10 x 30 m), four systems of soil management (CT, MT, NT and CNT) was studied. In subplots (10 x 10 m), the annual ryegrass was cropped for different purposes (C, G and S). The intensification of soil use due pasture or silage production during the winter cannot change macronutrient inputs in systems of soil tillage under high concentration of organic matter and acidity controlled. This can be state if the winter pasture to be adequately managed. The high DM and macronutrients accumulated in aerial part of maize show the ability of annual ryegrass for nutrient recycling on the systems of production with different tillage and conditions of lime reactivity.